THE DEVELOPMENT OF INDONESIAN LANGUAGE TEACHING MATERIALS BASED ON KNOWLEDGE INTEGRATION IN ISLAMIC HIGHER EDUCATION - Rahmiati Rahmiati; Azhar Arsyad; Muhammad Yaumi; Nur Asik; Muhammad Nur Akbar Rasyid (Universitas Negeri Makassar, 2019)
The Development of Indonesian Language Teaching Materials Based on Know-ledge Integration in Islamic Higher Education. This study aims at describing: (1) the reality and the needs for materials oriented towards knowledge integration, (2) the prototype and evaluation of the developed teaching materials. This is a Research and Development undertaken in UIN Alauddin Makassar involving 138 students, five lecturers, and two expert validators. The results show the currently used materials is not based on knowledge integration. Integration have been undertaken in the developed materials by including related verses or hadith, raising Islamic themes as reading materials and examples. The developed materials were evaluated by expert validators both content and design with the average score of 3.91 and 3.93 respectively and categorized as very good. The gain index for small and large groups is 0.71 and 0.72 respectively and categorized as high.